Relationships Between Effort, Rate of Perceived Exertion, and Readiness During a Warm-Up for High-Speed Sprinting - Roland van den Tillaar; Nick Ball; Per Øyvind Torvik (Journal of Functional Morphology and Kinesiology)
Objectives: The aim of this study was to investigate how a sprint warm-up with increasing prescribed effort relates to actual effort and how this influences RPE and readiness for a maximal 50 m sprint performance. Methods: A total of 19 subjects (17 men and 2 women age: 43.8 ± 12.6 yrs., height: 1.78 ± 0.08 m, body mass: 78.7 ± 9.5, 100 m PB: 13.07 ± 1.0) undertook a short specific warm-up of 8 × 50 m runs with 60 s rest in between (10 min in total) where a dynamic exercise was performed. The first 50 m run was performed at a self-estimated effort of around 60% of estimated maximal sprint speed. Each subsequent 50 m repetition required a 5% increase in sprint speed until it reached 95% of maximal self-estimated intensity, followed by a maximal 50 m sprint performance. Every 50 m time was measured together with the rating of perceived exertion (RPE) and readiness to perform a maximal 50 m sprint. Results: The main findings were that actual percentage of effort was generally higher than prescribed efforts, especially in the initial test, while alignment improved in the retest, except at higher intensities (80–90%). Furthermore, both RPE and readiness had a significant positive correlation with the percentage of effort, though RPE was consistently lower, and readiness was slightly reduced at lower efforts in the retest. In addition, test–retest reliability indicated consistent sprint performance and perceptual measures across sessions. Conclusions: It was concluded that this short, structured warm-up is suitable for maximal sprint performance as shown by the readiness and RPE.